The Relationship between the Built Environment and Climate Change: The Case of Turkish Provinces - Bektas, Yasin; Sakarya, Adem (MDPI, 2023)
The relationship between the built environment and climate change has been discussed from many perspectives. This study examines the effect of the built environment on climate change indicators in Turkish provinces over the last 18 years, contributing to the literature on built environment analyses regarding both urban and rural areas, unlike other studies that have focused mostly on urban areas. The study discusses the changes in climate indicators using maps and analyzes the effects of the built environment on climate change using linear regression. The results indicate that provinces in Turkiye have experienced climate change effects such as increased annual mean temperature, maximum temperature, maximum precipitation, extreme weather events, and drought. These effects differed both in terms of geography and the subperiods over the examined period. The results also demonstrate the increase in the built environment to have a positive correlation with the increases in annual maximum temperature and the annual number of extreme weather events. The built environment in Turkiye increased 63% between 1990 and 2018, and the average number of extreme weather events per province increased from 0.3 to 8 over this same period. At the same time, the average annual mean temperature increased from 12.9 to 15.1 degrees C, the average maximum temperature went up from 24.6 to 25.8 degrees C, the average annual maximum precipitation increased from 125.6 to 157.7 mm, and the average number of dry months per year increased from 3.4 to 3.8.
Keywords: climate change; built environment; urban; land use; Turkiye; LAND-USE CHANGE; EXTREME-WEATHER-EVENTS; REGIONAL CLIMATE; URBANIZATION; DEFORESTATION; TEMPERATURE; DYNAMICS; IMPACT; ZONES; Science & Technology - Other Topics; Environmental Sciences & Ecology